Physical aspects of stabling systems in agriculture as a precondition of efficient utility - PoÅ¡ivÃ¡kovÃ¡, TerÃ©zia; Hromada, Rudolf; Korim, Peter; PoÅ¡ivÃ¡k, JÃ¡n; Å vajlenka, Jozef; HorvÃ¡thovÃ¡, MargarÃ©ta (International Journal of Engineering and Technology, 2019)
The need to create an appropriate welfare environment for animals, as a health and high yield factor, is increasingly coming to the fore. The environment has a continuous and direct impact on animals that quickly starts to show in their utility and health. In this respect, it is animalsâ€™ immediate surroundings that play the most important role, i.e. the air in stables, also referred to as â€˜microclimateâ€™. For example, the temperature of the air in stables has a direct effect on metabolic intensity and animal production, and an indirect impact on their health and welfare. It is therefore important to take into account thermal relationships between animals and the air in stables, as well as thermal relationships between a microclimate and the surrounding environment. The aim of this article is to assess the temperature and humidity characteristics of the indoor environment of two stabling units with different breeds of animals, taking into account performance indicators for milk production.Â Â